Proliferative Glomerulonephritis With Monoclonal IgG3λ Deposits: A Case Report of a Rare Cause of Monoclonal Gammopathy of Renal Significance - Yu, Xiao-juan (Kidney Med, 2019)
Proliferative glomerulonephritis with monoclonal immunoglobulin G (IgG) deposits is a rare monoclonal gammopathy of renal significance with dense deposits on electron microscopy similar to polyclonal immune complex–mediated glomerulonephritis. 70% of patients with proliferative glomerulonephritis with monoclonal IgG are negative for a monoclonal (M) spike, and patients with this condition rarely develop an M spike during follow-up. We report a Chinese man in his 50s who presented with nephrotic syndrome and normal glomerular filtration rate. His first kidney biopsy showed masked IgG3 deposition, such that IgG3 staining was apparent only after digestion by enzyme on paraffin tissue, with a membranoproliferative pattern. During follow-up, his glomerular filtration rate worsened and proteinuria increased. 18 months after the first biopsy, the patient developed an M spike; a second kidney biopsy showed proliferative glomerulonephritis with monoclonal IgG deposits with unmasked IgG3λ deposition. The patient was successfully treated with bortezomib and dexamethasone, followed by lenalidomide and dexamethasone maintenance therapy.